Clinical and biochemical characteristics of women with menstrual disturbance - Szu-Yu Shen; Shih-Yi Huang; Ching-Hung Hsieh; Ming-I Hsu; Chih-Yu Cheng; Chun-Sen Hsu (Elsevier, 2014)
Objective: Menstrual irregularity is one of the major complaints in women of reproductive age. The aim of this study was to evaluate the complications in women with different menstrual disturbances. Materials and methods: This is a retrospective study. A total of 576 women were screened first, and 470 women were included later [257 women with oligo/amenorrhea (149 hyperandrogenic and 108 nonhyperandrogenic women) and 213 normocyclic controls]. Endocrine and metabolic parameters and insulin resistance were compared among different menstrual patterns. Results: The average duration of menstrual cycle length was positively correlated with age, levels of androgens and prolactin, lipid profiles, and the parameters of insulin resistance. Hyperandrogenic women with amenorrhea had higher levels of androgens and more lipid profiles disorders than hyperandrogenic women with oligomenorrhea. However, nonhyperandrogenic women with amenorrhea had a degree of insulin resistance and metabolic disturbance similar to that of nonhyperandrogenic women with oligomenorrhea. Interestingly, for women with normal prolactin levels, serum prolactin levels were significantly lower in amenorrhea than oligomenorrhea in both hyperandrogenic and nonhyperandrogenic groups. Conclusion: The degree of menstrual disturbances does not correlate with the severity of insulin resistance and metabolic disturbances in women without excess levels of androgen. For women with normal prolactin levels, amenorrheic patients had significantly lower serum prolactin levels than oligomenorrheic patients.